Field notes contributed by James J. Dinsmore, summer 1981 - Dinsmore, James J.et al (1981)
Summer report of birds contributed by James J. Dinsmore. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1981. Epson - sheet feed